Challenges towards serologic diagnostics of emerging arboviruses. (September 2021) - Fischer, Carlo; Jo, Wendy K.; Haage, Verena; Moreira-Soto, Andrés; de Oliveira Filho, Edmilson F.; Drexler, Jan Felix
Abstract: Background: Appropriate laboratory diagnostics for emerging arboviruses are key for patient management, surveillance and intervention, including molecular tests and serological tests detecting viral antigen or virus-specific antibodies. Objectives: We provide an overview of the challenges towards serological testing for the most important emerging arboviruses, including Zika, dengue and chikungunya viruses. Sources: We retrieved a data set on performance of commercially available antibody- and antigen-detecting tests from 89 peer-reviewed articles conducting a systematic literature research in PubMed. Content: We identified commonly used antibody- and antigen-detecting tests and analysed their overall performance. We discuss how timing of serological testing and the use of paired samples from acute and convalescent phases of infection are crucial to optimize diagnostic sensitivity and specificity. We then exemplify how serological diagnostics are challenged by the patient's infection history through the 'original antigenic sin' and cross-reactive antibodies in the context of global co-circulation of antigenically related viruses. We highlight how individual infection histories with different arboviruses and with other pathogens such as herpes viruses and Plasmodia can produce inaccurate test results. We show that rapid tests for antibody and antigen detection in point-of-care settings have a significantly lower sensitivity compared with laboratory-based tests such as ELISA. We show that the performance of antibody- and antigen-detecting tests varies greatly between tropical regions of endemic transmission and non-endemic regions. Finally, we highlight that test sensitivity and specificity have to be equilibrated carefully and frequently either of them must be prioritized over the other, depending on disease prevalence and intended use of tests. Implications: For reliable serological diagnostics, it is essential to be aware of inherent test limitations. Although multiplexed testing and testing of convalescence samples can improve diagnostic performance, global spread of (re-)emerging viruses requires careful implementation and evaluation of serological testing and unambiguous results may not always be achievable.